Development of a Nondestructive Impulse Device and Damage Model for Unreinforced Concrete. (2nd April 2012) - Boone, Shane D.; Barr, Paul J.; Bay, James A.; Halling, Marvin W.
Abstract : Unconstrained compression waves were measured using a newly developed, nondestructive, short impulse excitation device developed for long-term structural health monitoring. The measurements, using this innovative device, were used to determine the variation in the first longitudinal modal frequency as a function of loading magnitude and loading cycles to failure of various concrete mixes. Longitudinal frequency and cumulative energy variations were found to be a function of concrete compressive strength. These results imply that higher-strength concrete more easily absorbs energy and restricts the growth of microcracks. Based on the results, a new damage model is proposed that was shown to correlate with measured values to within 7%. This proposed model was found to have a closer correlation than Miner's hypothesis and damage index models from other reviewed research.